Lost in transition? Professional perspectives on transitional mental health services for young people in Germany: a qualitative study - Sabine Loos; Naina Walia; Thomas Becker; Bernd Puschner (BMC, 2018)
Abstract Background The transition of young patients from child and adolescent to adult mental health services often results in the interruption or termination of care. At this intersection, mental health professionals function as gatekeepers between systems, and their personal views on current clinical practice can contribute to a broader understanding of procedures and help identify reasons for service gaps. This qualitative study investigated the views of mental health professionals on services for young people during the transition from child and adolescent to adult mental health care, as well as on factors which facilitate or hinder continuity of care. Methods Four group discussions with 24 mental health professionals with various backgrounds were conducted. Groups were audio-taped, transcribed verbatim and analyzed following the reconstructive approach of R. Bohnsack's documentary method. Results A main theme and six subthemes emerged. Participants' overall concern was an increasing lack of patient centeredness in care provision. They criticized the limited flexibility and time constraints of their work, which was held to be incompatible with the time-consuming process of engaging young patients in care and coping with their individual needs. A lack of adequate interprofessional exchange and networking was seen as resulting in a diffuse sense of responsibility and a lack of clarity for all involved parties. Participants focused on the adverse impact of neglecting developmental characteristics in care procedures for young patients and revealed personal issues they experienced in their work with young patients (e. g. personal difficulties with diagnosing). Conclusions Mental health professionals at this transitional point face a number of complex tasks as well as limitations in terms of time and personal support. An emphasis should be placed on forming and maintaining partnerships within and between systems which could contribute significantly to relieving professionals' workload. Furthermore, an open style of communication to engage young patients in care is essential. Strengthening communicative skills, improving knowledge about this life stage (especially when working in adult services), and promoting interprofessional encounters can help to develop new procedures in clinical practice. On higher system levels, heightened awareness of the need to reduce fragmentation of care and administrative barriers is needed.